Introduction to the philosophy of the human person - Stephens, Sunil H. (Quezon City : Sibs Publishing House, Inc., 2019)
"This textbook deals with the Philosophy of the Human Person." Philosophy analyses our most basic concepts and beliefs. It critically evaluates these concepts and beliefs. Philosophy can therefore be seen as a discipline in itself as well as focusing on important areas of human thought and life: philosophy of religion, philosophy of science, Philosophy of art, and philosophy of history etc. this means the critical evaluation of the basic concepts and beliefs in each of these areas. The Philosophy of the Human Person therefore means analyzing the basic concepts regarding the human person."
Includes bibliography.
English text.
Keywords: Philosophical anthropology; Human behavior; Philosophy -- Textbooks